Pengaruh Persepsi Pengetahuan, Kemudahan Penggunaan, Dan Kemanfaatan Terhadap Minat Menggunakan Layanan Dompet Digital Bagi Generasi X Di Medan - Khairina, Nabila; Harahap, Muhammad Ikhsan; Yanti, Nursantri (Universitas Hamzanwadi, 2024)
This research aims to analyze the influence of perceived knowledge, ease of use, and usefulness on interest in using digital wallet services for Generation X in Medan. The research method used was quantitative with survey techniques by distributing questionnaires to 100 respondents who were included in the Generation X category in Medan. The data analysis technique used is multiple linear regression to determine the influence of the three independent variables on interest in using digital wallets. Processed using IBM SPSS Statistics version 29 as an analytical tool. The results of this research are that simultaneously, these three variables (perceived knowledge, ease of use, and usefulness) have a significant effect on interest in using digital wallet services. Meanwhile, partially, perceived knowledge and ease of use have no effect on interest in using digital wallet services for Generation X in Medan. Meanwhile, usefulness influences interest in using digital wallet services for Generation X in Medan. Following up on the findings of this research, to increase the adoption of digital wallet services among Generation.